STUDY OF THE RATES OF BIMOLECULAR IONIC REACTION BETWEEN DIBROMOSUCCINATE ANDHYDROXIDE IONS - Uddin, Fahim; Tahir, Hajira; Nisa, Noor-un- (Biological Sciences - PJSIR, 2001)
The effect of dielectric constant (B) and solvent effects on the rates of bimolecular ionic reaction between dibromosuccinate and hydroxide ions have been studied. Two mixed solvents i.e. water-ethanol and water-methanol were used for the measurements of the effect of dielectric constant. The rate constants in different aquo-organic mixtures have been found to lie in the order methanol> ethanol. The radii of the activated complex for water-ethanol and water-methanol media have been evaluated from the slopes of the plots of logarith of rate constant at zero ionic strength (log ko) and reciprocal of the dielectric constant (lIB). It is established that the shape of the activated complex in aquo-organic mixtures is similar to Laider-Eyrings approach of single sphere model in this particular reaction.